GENERATE ELECTRICITY BY WASTE MATERIALS - Manish Kumar; Chandan Kumar; Sani Kumar Patel; Nitish Kumar Gupta; Shaikh Z.A.R. (International Journal of Innovations in Engineering Research and Technology, 2023)
In This Project We use waste materials for generate Electricity We show in this project one Electricity generating zaar box when we have waste materials like plastic, paper and other Then we burn that Materials in zaar box and when burning start then heat going to heating penal then heating penal convert the heat into Electricity Then we store that Electricity in battery and use that Electricity for bulb glowing and many others work